1999
DOI: 10.1038/sj.onc.1202752
|View full text |Cite
|
Sign up to set email alerts
|

Repression of an alternative mechanism for lengthening of telomeres in somatic cell hybrids

Abstract: Some immortalized cell lines maintain their telomeres in the absence of detectable telomerase activity by an alternative (ALT) mechanism. To study how telomere maintenance is controlled in ALT cells, we have fused an ALT cell line GM847 (SV40 immortalized human skin ®broblasts) with normal ®broblasts or with telomerase positive immortal human cell lines and have examined their proliferative potential and telomere dynamics. The telomeres in ALT cells are characteristically very heterogeneous in length, ranging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
2
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 37 publications
4
85
2
1
Order By: Relevance
“…Inhibition of telomerase will put tumors that are initially telomerase positive under strong selection pressure to activate ALT. Because repression of ALT results in senescence and cell death (Nakabayashi et al 1997;Perrem et al 1999), ALT, like telomerase, may be an attractive drug target. The use of both classes of drugs to inhibit telomere maintenance in tumor cells may help prevent the emergence of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of telomerase will put tumors that are initially telomerase positive under strong selection pressure to activate ALT. Because repression of ALT results in senescence and cell death (Nakabayashi et al 1997;Perrem et al 1999), ALT, like telomerase, may be an attractive drug target. The use of both classes of drugs to inhibit telomere maintenance in tumor cells may help prevent the emergence of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Although ALT is characterized by the presence of elongated and heterogeneous telomeres in the absence of TA, [11][12][13] it has also been shown that a small proportion of telomerase positive tumors may exhibit an ALT TRF pattern. 12 Perrem et al 39 demonstrated that the ALT telomere phenotype was abrogated in cell hybrids between ALT and telomerase-positive cells. Thus, this would indicate that our 3 telomerase-positive tumors contained subpopulations of cells using telomerase or ALT for maintaining telomere length.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of these genes may act through other pathways because the mortal phenotype can be restored in somatic cell hybrids despite the presence of telomerase activity (as detected by an in vitro assay, which does not necessarily re¯ect continuing telomerase activity at the telomere) . That ALT results from recessive mutation(s) was demonstrated by the observation that fusion of an ALT+ immortal cell line with normal cells resulted in senescent hybrids that had lost the ALT telomere phenotype (Perrem et al, 1999). Further, some telomerase-positive immortalized cells appear to contain repressors of ALT activity: ALT was repressed in immortal hybrid cells formed by fusing an ALT+ cell line from immortalization complementation group A with either of two telomerase-positive cell lines from the same complementation group (Perrem et al, 1999.…”
Section: Alt Genetics and Repressionmentioning
confidence: 94%
“…That ALT results from recessive mutation(s) was demonstrated by the observation that fusion of an ALT+ immortal cell line with normal cells resulted in senescent hybrids that had lost the ALT telomere phenotype (Perrem et al, 1999). Further, some telomerase-positive immortalized cells appear to contain repressors of ALT activity: ALT was repressed in immortal hybrid cells formed by fusing an ALT+ cell line from immortalization complementation group A with either of two telomerase-positive cell lines from the same complementation group (Perrem et al, 1999. In contrast, fusion of ALT+ and telomerase-positive cell lines from immortalization complementation group D resulted in immortal hybrids , and by PD 77 a few weeks later immortalized cells had overgrown the culture; telomerase activity was not detectable at any time (Yeager et al, 1999).…”
Section: Alt Genetics and Repressionmentioning
confidence: 99%